The Red Book: Architecture, Collaboration, and the Osaka Expo ’70 - Aragüez, Marcela (Actar Publishers, 2026)
This volume centers on the Red Book, a little-known 1967 research document that served as the conceptual foundation for Festival Plaza, the central space of Expo ’70 in Osaka. Produced by an extraordinary coalition of architects, artists, engineers, computer scientists, musicians, and writers, the Red Book proposed a radically new form of public space—adaptive, participatory, and technologically responsive. It offers a compelling vision of 1960s Japan as a site of experimental thought and interdisciplinary collaboration. Among other things, it reveals how traditional cultural forms such as festivals were translated into spatial strategies, merging local knowledge with global currents in cybernetics, media theory, and performance. By translating the Red Book for the first time and situating it within architectural, technological, and cultural histories, this publication brings to light a foundational yet overlooked source in the making of modern Japan. Drawing on perspectives from architecture, religious studies, media theory, and urban planning, the volume unpacks the Red Book’s innovative approaches to design, participation, and control. It challenges dominant narratives of Expo ’70 and broadens the cast of contributors recognized in postwar architectural history. In an era of renewed interest in responsive environments and public space, and particularly in the aftermath of Expo 2025, this work offers timely insights into how past visions of the future were crafted through collective research and creative foresight. It will be of relevance to architects, designers, engineers, artists, scholars, and students across disciplines who are seeking to understand the cultural and technological imagination of the 1960s and its lasting impact on how we conceive, build, and manage collective space today.
Keywords: 62 Ciencias de las Artes y las Letras::6201 Arquitectura; ODS 11 - Ciudades y comunidades sostenibles